Implementing an efficient expert system for services center management by fuzzy logic controller - Abd Ghani, Mohd Khanapi; Mohammed, Mazin Abed; Ibrahim, Mohammed S.; Mostafa, Salama A.; Ahmed Ibrahim, Dheyaa (Little Lion Scientific, 2017)
Expert System (ES) is considered to be the prominent reasoning practices which are commonly employed towards various application domains. Considering expert systems, human understanding regarding specific proficiency in accomplishing specific tasks could be signified as facts and rules towards their knowledge base, which finds and employs the data delivered by means of a manipulator. Reasoning procedure has been further employed towards the specified expertise by means of heuristic methods for formulating the elucidation. Mechanisms which employ knowledge based approaches are considered to be more candid when compared to other conservative approaches. Knowledge could be signified clearly towards knowledge base, thereby capable in alteration with comparative easiness, which commonly employs the concept of rules. Inference engines employ knowledge base subjects for solving specific problems based on user responses by means of interface (for instance, specify the situations needed for car assessment). This inference unit deeds with knowledge for applying this knowledge for specific problems. There are numerous approaches for control systems that are applied in all the major areas in industry. In all these approaches for controlling the systems, fuzzy has been deemed to be the best methodology, mainly because of its increased speed and cost-efficiency. For machine regulation, fuzzy logic is found to be vividly employed. This paper mainly focuses in designing the simulation model for fuzzy logic regulator in advising the supervisor of service center in maintaining definite delay in service towards acceptable limits